Sappho: Fragments. - Goldberg, Jonathan (punctum books, 2018)
In Sappho, Jonathan Goldberg takes as his model the fragmentary state in which this sublime poet's writing survives, a set of compositional and theoretical resources for living and thinking in more fully erotic ways in the present and the future. This book thus offers fragmentary commentary on disparate (Sapphic) works, such as the comics of Alison Bechdel, the paintings and cartoons of Leonardo da Vinci, Robert Reid-Pharr's "Living as a Lesbian," Madeleine de Scudéry's Histoire de Sapho, John Donne's "Sapho to Philaenis," Todd Haynes and Patricia Highsmith's Carol, Virginia Woolf's Orlando, writings by Willa Cather, and the paintings and writings of Simeon Solomon, among other works. Goldberg challenges readers to imagine and experience what Sarah Orne Jewett named the "country of our friendship," a love both exceedingly strange and compellingly familiar. Just as Sappho's coinage "bitter-sweet" describes eros as inextricably contradictory -- two things at once, one thing after another, each interrupting, complicating, each other -- the juxtapositions in this book mean to continually call into question categories of identity and identification in the wake of a quintessential woman writer from Lesbos. Over and over again, Goldberg's Sappho: ]fragments inquires into how race, sexuality, and gender cross each other. The theoretical genius of Eve Kosofsky Sedgwick presides over this set of meditations and mediations on likeness and desire. Rather than homogenizing its many subjects, it invites the reader to explore and inhabit new transits within and through what Audre Lorde called "the very house of difference."